Comparative study between stapled versus hand sewn method for large bowel anastomosis surgery. - Al-aubaidi, Tariq E. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: intestinal anastomosis is one of the most commonly performed procedures it required to reestablish gastrointestinal continuity after surgical resection, traumatic disruption or bypass procedures. In last decade, advances in intestinal stapling devices have led to an increased frequency of stapled anastomosis. There are varieties of proposed benefit from a stapled technique: better blood supply, reduced tissue manipulation, less edema, uniformity of suture, adequate or perhaps wider lumen at the site of anastomosis, ease and rapidity.Patient and methods: a prospective study was conducted on 103 patients who suffered from benign and malignant diseases in addition to trauma patients. They were divided in to two groups (SA)(stapled group) which involved 51 patients where the anastomosis were done by stapler and other group of 52 patients where the anastomosis were done by hand sewing named as HS group (hand sewing group). Both groups had the same preoperative characters such as age and gender, and the types of outcome analyzed were specific mortality, clinical anastomotic leak, stricture, anastomotic hemorrhage, reoperation, wound infection and hospital stay. Results: A total of 9 patients (17.6%) in SA group developed complications compared to 20 patients (38.5%) in HS group (p-value 0.019). nine patients developed fistula in HS group (17.3%) compared to two patients (3.9%) in SA group (p- value 0.035). mean postoperative hospitalization time for SA group (6.5) days while for HS group (8.8) days (p-value 0.75) . there is a significant difference regarding fistula in favor of stapled anastomosis .Conclusion: staples anastomosis is safe and effective and associated with fewer leaks than hand sewn anastomosis.